Direitos humanos, diversidade, gênero e sexualidade reflexões, diagnósticos e intervenções na pesquisa em educação - Silva, Matheus Estevão Ferreira da (Editora Oficina Universitária, 2020)
This collection is born from the attempt to disseminate results of research carried out within the scope of the Graduate Program in Education (PPGE) of the Faculty of Philosophy and Sciences (FFC), of the São Paulo State University "Júlio de Mesquita Filho" (UNESP), Campus of Marília, which address the intersection of human rights and themes related to human diversity - with the theme in the themes of gender and sexuality - with Education. The book is guaranteed in two parts: the first contains 07 texts that deal with Human Rights, Dignity, Diversity and Education, showing the relationship between human rights and Education and their intersection with the issue of diversity. In the second part, which brings together 08, the theme generating the analyzes was Human Rights, Gender, Sexuality and Education, focusing on the themes of gender and sexuality and, respectively, the rights of women, the LGBTQIA+ population (lesbians, gays, bisexuals, transsexuals, transvestites, transgenders, queers, intersex, asexuals, etc.). Studies and Post-Doctorates, in progress or completed, 13 of which were authored by PPGE students and another 02 texts written by invited professors, also involved with the PPGE. Their discussions vary from theoretical reflections to diagnoses or interventions in different perspectives and educational realities.